Hospital Regional Docente Categoría III-1 MINSA, Trujillo – La Libertad - Ruiz Ruiz, Johan Irvin (2023)
Hospitals play a fundamental role in meeting the growing need for adequate health care, needs that demand humanized services for the patient, environmentally friendly and adequate care capacity for complex pathologies that a category III-1 hospital in the city of Trujillo demands. However, this evolution is not seen in the current Regional Teaching Hospital of Trujillo, since the facility has substantial and determining deficiencies for the proper development and care of health needs. This led to the conception of this research and its subsequent architectural proposal. The proposal for the new Regional Teaching Hospital of Trujillo responds to the main problem of the current hospital's deficient infrastructure, coverage and provision of health services, which affects patients, the public and health professionals. All this prevents the proper provision of health care, affecting the health and integrity of the population assigned to this facility. Therefore, this hospital project seeks to mark a milestone in the development of hospitals in Peru, both in the form and functional development of the same, having as fundamental design criteria the typological identity that identifies a health facility of high complexity, universal accessibility to users, sustainability and energy efficiency and humanization of hospital spaces. This allows to achieve adequate access, stay, care, diagnosis, treatment and recovery of each user involved.